The Relationship between Internet-based Entertainment and Self-expectations in Education in Adolescents: The Moderating Effect of Parenting Styles - He, Xiaobin (Best Evidence in Chinese Education, 2025)
Drawing on personal and household data from the China Family Panel Studies (CFPS) 2020, the study aims to examine the relationship between internet-based entertainment and self-expectations in education in adolescents, as well as analyzing the moderating effects of various parenting styles on this relationship. Its research findings reveal that internet use for entertainment purposes, such as online gaming and short-video viewing, can markedly undermine educational aspirations in adolescents; and that parenting styles have no significant influence on the negative effect of frequent short-video viewing on educational aspirations in this group, whereas tolerant parenting can suppress the negative effect of frequent online gaming, as opposed to neglectful parenting.